Exploring adoption dynamics - Samuel Musungwini; Izak van Zyl; Jan Kroeze (South African Computer Journal)
There is a lack of acceptance, adoption and sustained use of mobile phones for agricultural purposes by smallholder farmers in  Zimbabwe, but the reasons for this have not been critically explored. In this study, the authors used a naturalistic methodology to help  uncover the nuances of adoption dynamics among smallholder farmers in Gokwe South District, Zimbabwe. Data was gathered  from in-depth interviews and focus groups. The findings suggest that gender, age, land ownership size, farming experience, mobile  device ownership, and the period of owning a mobile device are critical precursors to adoption and use. Furthermore, digital  proficiency and literacy, affluence, mobile technology services cost and telecommunication infrastructure availability are vital in  achieving continuous, sustainable use of mobile technology in the Zimbabwean agricultural sector. This research has practical  implications for policy and practice and may inform national legislation encouraging the increased use and affordability of mobile  devices in the local agricultural sector. The research also makes a theoretical contribution in terms of unpacking the key factors that  inhibit the adoption of mobile technology in marginalised settings.